KASIH ALLAH DALAM KESEMBUHAN:: ANALISIS STUDI LITERATUR TEOLOGI DAN EMPIRIS TENTANG KARUNIA DAN ANUGERAH - Nunuk Novianti (STT-RAI Batam, 2025)
This study analyzes the concept of “God’s Love in Healing,” highlighting how God’s love is manifested through gifts and grace experienced by believers. The background of this research addresses ongoing doubts and diverse perspectives among Christians regarding the reality of healing gifts in the present era, as well as the need for a more holistic understanding of the integration between religious experience and empirical evidence in the healing process. Employing a qualitative method with descriptive analysis and literature review, this research combines theological sources (the Bible, theological books) and empirical studies from relevant journals. The findings reveal that God’s love in healing is not limited to physical recovery but also encompasses spiritual, mental, and social dimensions. The gift of healing, as described in 1 Corinthians 12:9, is a manifestation of God’s love that can be experienced by every believer according to His sovereignty, both through miracles and medical interventions. God’s grace serves as the primary foundation in the entire healing process, where the experience of healing often leads to transformation of faith, character, and social relationships. Thus, the experience of healing for believers is an integral part of God’s love that is real and relevant in daily life, providing hope and strength for Christian communities amid the challenges of the modern era.